2011
DOI: 10.1038/ismej.2011.116
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the complex sponge microbiota: core, variable and species-specific bacterial communities in marine sponges

Abstract: Marine sponges are well known for their associations with highly diverse, yet very specific and often highly similar microbiota. The aim of this study was to identify potential bacterial sub-populations in relation to sponge phylogeny and sampling sites and to define the core bacterial community. 16S ribosomal RNA gene amplicon pyrosequencing was applied to 32 sponge species from eight locations around the world's oceans, thereby generating 2567 operational taxonomic units (OTUs at the 97% sequence similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
554
4
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 464 publications
(601 citation statements)
references
References 68 publications
34
554
4
9
Order By: Relevance
“…The core microbiome of sponges has also recently been characterized and, again, core members depended on the cutoff used (Schmitt et al 2012). At 97% cutoff only three core phylotypes were identified, increasing to eight when a 95% cutoff was used, and 18 at 90% (Schmitt et al 2012). In this study, only five phylotypes were identified as core using the 90% cutoff (Pseudomonas, two cyanobacteria, Propionibacterium and Rothia).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The core microbiome of sponges has also recently been characterized and, again, core members depended on the cutoff used (Schmitt et al 2012). At 97% cutoff only three core phylotypes were identified, increasing to eight when a 95% cutoff was used, and 18 at 90% (Schmitt et al 2012). In this study, only five phylotypes were identified as core using the 90% cutoff (Pseudomonas, two cyanobacteria, Propionibacterium and Rothia).…”
Section: Discussionmentioning
confidence: 61%
“…However, in the same study there was no single abundant bacterial species (defined as [0.5% of the community) shared by all 154 individuals studied. The core microbiome of sponges has also recently been characterized and, again, core members depended on the cutoff used (Schmitt et al 2012). At 97% cutoff only three core phylotypes were identified, increasing to eight when a 95% cutoff was used, and 18 at 90% (Schmitt et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Encompassing 3321 unique OTU 0.03 from 19 described bacterial phyla, 14 candidate bacterial phyla and 3 described archaeal phyla, the ascidian microbiota exhibited comparable diversity to the rich microbiota associated with marine sponges (Schmitt et al, 2012) and corals (Sunagawa et al, 2010) and indicates that the ascidian tunic represents a previously unrecognized hotspot for marine microbial diversity. Visualization of microbial cells by transmission electron microscopy confirmed the presence of microbes in the ascidian tunic and was consistent with results from 16S rRNA gene tag pyrosequencing, for example, the prevalence of cyanobacterial OTUs (450% of sequence reads) and cyanobacterial cells encased in a fiber network in Pycnoclavella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Sub-sampling of sequence pools from samples with greater than 2000 reads were performed in the mothur software package to standardize sampling effort and determine its effect on diversity estimates. Host-specificity of the ascidian microbiota was assessed by partitioning OTUs into core (present in 470% of host species), variable (present in at least two host species) and specific (present in a single host species) groups (sensu Schmitt et al, 2012). To broaden the analysis of the specificity of the ascidian microbiota, abundant ascidian-associated OTUs (i.e., those represented by 4100 total sequence reads) were compared to sequences in the GenBank database using a nucleotide-nucleotide BLAST search (Altschul et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…이는 해삼과 새우에서 미분류군이 많은 이 유를 설명해 준다. 실제로 해면과 같은 해양 무척추 동물의 경우 에도 기존에 분류학적으로 알려지지 않은 많은 수의 서열들이 발견되고 있다 (Schmitt et al, 2012). 예를 들어 "Poribacteria" 와 같은 그룹은 해면에서만 특이적으로 발견되는 문으로서 아직 까지 순수 배양이 된 균주가 없기 때문에 후보 문(candidate phylum)으로만 정의 되어 있다 (Fieseler et al, 2004 …”
Section: 차세대 서열 분석법의 하나인 병렬 대용량 파이로서열 분석unclassified